2023
DOI: 10.1002/mp.16290
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of shielding designs for a cabinet form factor preclinical MV‐energy photon FLASH radiotherapy system

Abstract: Purpose A preclinical MV‐energy photon FLASH radiotherapy system is being designed at Stanford and SLAC National Accelerator Laboratory. Because of the higher energy and dose rate compared to conventional kV‐energy photon laboratory‐scale irradiators, adequate shielding in a stand‐alone cabinet form factor is more challenging to achieve. We present a Monte Carlo simulation of multilayered shielding for a compact self‐shielding system without the need for a radiation therapy vault. Methods A multilayered shield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In all cases, the multilayered design resulted in lower effective dose rates by ~20% when compared to the single-layer design while occupying the same volume. This agrees with previous results reported by Rosenstrom et al (2023) in which the multilayered shielding design proved to be more efficient.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In all cases, the multilayered design resulted in lower effective dose rates by ~20% when compared to the single-layer design while occupying the same volume. This agrees with previous results reported by Rosenstrom et al (2023) in which the multilayered shielding design proved to be more efficient.…”
Section: Resultssupporting
confidence: 93%
“…The effect of the multilayered shielding methodology (Rosenstrom et al 2023) was confirmed in simulations where it was applied to the treatment head shielding with a 19% reduction in the effective dose rate in the Control Room, as well as a reduction in the effective dose rate at all points of interest. Additionally, mass and volume reductions can be performed with the multilayered design resulting in small and lighter treatment head shielding.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The UHDR of FLASH therapy presents new challenges, such as the need for a new shielding system. MC simulation can provide a solution for simulating such a shielding system, as explored in a study [27]. Another investigation focused on ionizing radiation acoustic imaging through simulation and its potential as a dosimetric tool for FLASH RT.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%